Edward Said's Theory of Mind - Bedjaoui, Kheira; Majdoubeh, Ahmad (Dirasat: Human and Social Sciences, 2023)
Objective: This paper aims to explore Edward Said's Theory of Mind, with a particular focus on his famous book, "Beginnings, Intention, and Method" (1975). Methods: The paper delves into an analysis of Said's work "Beginnings" from a philosophical perspective. It specifically investigates Said's relationship to eminent thinkers such as René Descartes, Ludwig Wittgenstein, Georg Von Leibniz, Bertrand Russell, and other influential figures whom Said held in high regard. Results: The study reveals that Said aligns himself more with Modern Western Philosophers than with literary Western theorists. It highlights Said's rejection of Foucault's ideas and his alignment with Derrida. Moreover, Said emerges as a representative of Nahda intellectuals, advocating for writing as a means to speak truth to power. It found that Said was more of a philosopher than a literary theorist. Said introduced literary theorists because he wanted to exclude them from literary academia. In Said’s mind, literary theorists have presented knowledge as a discontinuity rather than a continuity to disrupt the consciousness of the Arabs. Conclusion: The study concludes that Edward Said can be more accurately characterized as a philosopher rather than a literary theorist